Cognitive Trajectory Phenotypes in Human Immunodeficiency Virus–Infected Patients. (1st September 2019) - Dastgheyb, Raha M.; Sacktor, Ned; Franklin, Donald; Letendre, Scott; Marcotte, Thomas; Heaton, Robert; Grant, Igor; McArthur, Justin C.; Rubin, Leah H.; Haughey, Norman J.
Abstract : Objective: The presentation of cognitive impairments in HIV-infected individuals has transformed since the introduction of antiretroviral therapies. Although the overall prevalence of cognitive impairments has not changed considerably, frank dementia is now infrequent, and milder forms of cognitive impairments predominate. Mechanistic insights to the underlying causes of these residual cognitive impairments have been elusive, in part due to the heterogenous etiology of cognitive dysfunction in this population. Here, we sought to categorize longitudinal change in HIV-infected patients based on the performance in specific cognitive domains. Design: This study consisted of 193 participants from the CHARTER cohort with detailed demographic, clinical, and neuropsychological testing data obtained from 2 study visits interspersed by ∼6 months. Cognitive testing assessed executive function, learning and delayed recall, working memory, verbal fluency, speed of information processing, and motor skills. Change scores were calculated for each domain between the 2 study visits. Dimension reduction and clustering was accomplished by principal component analysis of change scores and k-means clustering to identify cognitive domains that group together and groups of subjects with similar patterns of change. Results: We identified 4 distinct cognitive change phenotypes that included declines in: (1) verbal fluency, (2) executive function (3) learning and recall, and (4) motor function, with approximately equal numbers of participants in each phenotype. Conclusions: Each of the 4 cognitive change phenotypes identify deficits that imply perturbations in specific neural networks. Future studies will need to validate if cognitive change phenotypes are associated with alterations in associated neural pathways.